P4.17 Contraceptive preference among female sex workers in the sivet study in nairobi, kenya. (8th July 2017) - Nyaoke, Borna
Abstract : Introduction: Long-acting reversible contraceptives (LARCs) are effective birth control methods that do not depend on patient compliance. They include injections, intrauterine devices (IUDs) and sub-dermal implants. Kenya had over 1.5 million people living with HIV in 2015 with female sex workers (FSWs) known to be at a higher risk for both unintended pregnancies and HIV infection. HIV clinical trials test novel compounds whose effects in fetuses are unknown thus require female subjects to use LARCs to avoid pregnancies. Clinical trials also aim to recruit high-risk individuals to closely study infection dynamics in a representative natural infection cohort. Therefore, it is crucial to investigate the preference for contraception in a HIV-high risk population such as FSWs to inform the design and conduct of HIV vaccine clinical trials, especially in the resource-limited Sub-Saharan Africa. The on-going Simulated Vaccine Efficacy Trial (SiVET) Study at KAVI-ICR may provide answers to this. Methods: Data on use of modern contraception methods (pills, injectables, implants, IUDs and surgicals) are collected from FSWs during screening, and confirmed by a contraceptive card or the presence of an implant or IUD strings. The proportion of women per method used is determined. Results: Seventy nine women with an age range of 18–50 years have been screened since 2016. Most (89%, n=73) were already using contraception. Of these; 63% (n=46) were on injectables, 22% on implants (n=16), 8% IUCDs (n=6), 4% pills (n=3) and 3% (n=2) had undergone a surgical method. No pregnancy while two HIV infections were reported at screening. Conclusion: There is high contraceptive use among the FSWs with the majority preferring injectables. This practice is encouraging and thus, discontinuation of volunteers from the clinical trial due to pregnancy is unlikely. At the end of trial in 2018, data will be collected on changes in contraceptive, number of pregnancies, condom use, HIV infections and experience on use of the contraception.